Perbedaan Kemampuan Literasi Sains dan Kognitif menggunakan Pembelajaran Kooperatif Tipe Jigsaw dan Group Investigation - M. Arifky Pratama; Iin Permatasari; Indra Indra; Yetri Pitriani; Zannatun Na’imah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine differences in scientific and cognitive literacy skills using jigsaw cooperative learning and Group Investigation. This type of research is a quasi-experimental research (Quasi Experiment). By using research design Non-Randomized Control-Group Pretest-Posttest Design. The sample of this study was 54 students who were divided into 3 groups, namely the experimental group using Jigsaw learning type, Group Investigation type learning and the control group. The data analysis technique used to test the hypothesis in this study used ANOVA. The results showed that the Group Investigation learning model was better in improving students' scientific literacy skills than the Jigsaw and Conventional learning models. Statistical tests show that there is a significant difference between students' scientific and cognitive literacy skills in integrated science subjects using the Jigsaw, Group Investigation and Conventional Cooperative models with a significance value of 0.000, meaning that the difference is very significant. Keywords: Cognitive, Group Investigation, Jigsaw, Scientific Literacy